Hubungan Asupan Protein, Vitamin A, Zink, dan Fe dengan Kejadian Stunting Usia 1-3 Tahun - Kundarwati, Ria Agus; Dewi, Afiska Prima; Abdullah, -; Wati, Desti Ambar (Universitas Muhammadiyah Semarang, 2022)
Stunting is a condition in which toddlers have a length or height that is less than their age. The purpose of this study was to determine the relationship between intake of protein,vitamin A, zinc, and iron with the incidence of stunting in children aged 1-3 years. The design used in this study is quantitative by using the Case Control approach. Subjectsinvolved in the study were 60 toddlers aged 1-3 years. 30 toddlers as the case group and 30toddlers as the control group at the North Raman Health Center, East Lampung Regency.Bivariate analysis in this study used the Chi Square Test.The results of the analysis using the Chi Square test showed that there was a relationshipbetween protein intake and the incidence of stunting (p = 0.000); there is a relationship betweenzinc intake and the incidence of stunting (p = 0.001); there is a relationship between BSI intakeand the incidence of stunting (p = 0.005). However, there was no relationship between vitamin Aintake and the incidence of stunting (p = 0.078). The conclusion of the research that the genesisof stunting was correlated to the intake of protein, zinc and iron but it was not correlated to theintake of vitamine A.Keywords: Stunting, Protein, Vitamin A, Zinc, and Iron